Is a CT-scan of the medial clavicle epiphysis a good exam to attest to the 18-year threshold in forensic age estimation?. (March 2016) - Houpert, Tyffanie; Rérolle, Camille; Savall, Frédéric; Telmon, Norbert; Saint-Martin, Pauline
Abstract: Computed tomography (CT) scan of the medial clavicular epiphysis is one of the methods recommended by the Study Group on Forensic Age Diagnostics to estimate the age of living individuals. The aim of our study was to assess the relationship between the skeletal maturation of the sternal end of the clavicle and the chronological age in a sample of French individuals, using a nine-stage classification. We retrospectively reviewed 319 chest CT-scans of individuals aged 15–30 years old (252 males, 67 females). Among males and females, all individuals with a complete fusion, or an ongoing fusion of more than one third of the total surface of the metaphysis were at least 18 years old. Our results were consistent with data in the literature indicating that individuals with a complete fused clavicle were at least 18 years old. Similar studies with the same methods allow for creating a database of samples from different countries to confirm the validity of this method and its excellent results in forensic age estimation of living individuals.